K63-linked ubiquitination of DYRK1A by TRAF2 alleviates Sprouty 2-mediated degradation of EGFR - Pengshan Zhang; Zhe Zhang; Yinkun Fu; Ying Zhang; Michael P. Washburn; Laurence Florens; Min Wu; Chen Huang; Zhaoyuan Hou; Man Mohan (Cell Death and Disease, 2021)
Abstract Dual specificity tyrosine phosphorylation regulated kinase 1A, DYRK1A, functions in multiple cellular pathways, including signaling, endocytosis, synaptic transmission, and transcription. Alterations in dosage of DYRK1A leads to defects in neurogenesis, cell growth, and differentiation, and may increase the risk of certain cancers. DYRK1A localizes to a number of subcellular structures including vesicles where it is known to phosphorylate a number of proteins and regulate vesicle biology. However, the mechanism by which it translocates to vesicles is poorly understood. Here we report the discovery of TRAF2, an E3 ligase, as an interaction partner of DYRK1A. Our data suggest that TRAF2 binds to PVQE motif residing in between the PEST and histidine repeat domain (HRD) of DYRK1A protein, and mediates K63-linked ubiquitination of DYRK1A. This results in translocation of DYRK1A to the vesicle membrane. DYRK1A increases phosphorylation of Sprouty 2 on vesicles, leading to the inhibition of EGFR degradation, and depletion of TRAF2 expression accelerates EGFR degradation. Further, silencing of DYRK1A inhibits the growth of glioma cells mediated by TRAF2. Collectively, these findings suggest that the axis of TRAF2–DYRK1A-Sprouty 2 can be a target for new therapeutic development for EGFR-mediated human pathologies.